A facile method to fabricate monolithic alumina–silica aerogels with high surface areas and good mechanical properties. Issue 6 (June 2020) - Peng, Fei; Jiang, Yonggang; Feng, Junzong; Li, Liangjun; Cai, Huafei; Feng, Jian
Abstract: In this study, monolithic alumina–silica aerogels with high surface areas and good mechanical properties were synthesized via a facile sol–gel method without solvent exchange. Furthermore, surface areas, microstructures (up to 1300 °C), and mechanical properties of the prepared alumina–silica aerogels were investigated. The sintering and phase transformations of metastable alumina nanoparticles are suppressed owing to the uniformly distributed Si in the alumina–silica aerogels; therefore, the alumina–silica aerogels can maintain much higher specific surface areas after being calcined at 800 °C (575.5 m 2 /g), 1000 °C (443.2 m 2 /g), and 1200 °C (120.6 m 2 /g) compared to pristine alumina aerogels. In addition, the prepared high surface area alumina–silica aerogels show considerably higher strengths than those obtained in previous works. The compressive stress (3 % strain) and elastic modulus of the alumina–silica aerogels reached 1.78 and 65.6 MPa, respectively. The reported alumina–silica aerogels in this study can be good candidates as high-temperature thermal insulators and catalysts.